Some New Theoretical Work on Half Butterfly Method for Hamiltonian Circuit in Complete Graph - Mohd Darus,, Maizon; Ibrahim, Haslinda; Karim, Sharmila (UTM Press, 2017)
A new method to construct the distinct Hamiltonian circuits in complete graphs is called Half Butterfly Method. The Half Butterfly Method used the concept of isomorphism in developing the distinct Hamiltonian circuits. Thus some theoretical works are presented throughout developing this method